2017
DOI: 10.1177/1078155217703792
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an integrated oral chemotherapy program on patient adherence

Abstract: As the use of oral chemotherapy continues to rise, the issue of patient adherence is a concerning aspect of cancer treatment. In this concurrent prospective and retrospective study, we assessed oral chemotherapy adherence in patients receiving their prescriptions at an institutional specialty pharmacy, with an integrated oral chemotherapy program. The primary endpoint is medication possession ratio. Secondary endpoints include self-reported adherence comparing survey data before and after the introduction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 11 publications
0
33
1
Order By: Relevance
“…A recent study that evaluated the effectiveness of an integrated oral chemotherapy program concluded that patients who were called twice a month to discuss their oral oncolytic had better adherence rates to their therapy than did patients who were not pre-emptively contacted. 57 …”
Section: Monitoring and Follow-upmentioning
confidence: 99%
“…A recent study that evaluated the effectiveness of an integrated oral chemotherapy program concluded that patients who were called twice a month to discuss their oral oncolytic had better adherence rates to their therapy than did patients who were not pre-emptively contacted. 57 …”
Section: Monitoring and Follow-upmentioning
confidence: 99%
“…Additionally, improved adherence has been observed among patients who follow up with a pharmacist within the first 3 months of oral chemotherapy [24].Results of numerous studies have demonstrated the impact of a pharmacist on adherence rates among patients on oral anticancer treatment. New research assessing the feasibility of an adaptive oral chemotherapy program showed that patients who were called to evaluate their oral oncolytic twice a month had greater adherence rates than patients who were not proactively approached [27].For patients with chronic immune thrombocytopenia, pharmacists may collaborate with the treatment team to offer continuous adherence assessments.…”
Section: Oncology Pharmacists'role In Patient Carementioning
confidence: 99%
“…Adherence to OA is an important indicator of therapeutic response 2,3,6,8,9 . Several studies have shown that poor adherence may affect treatment efficacy, toxicity, public health expenditures, patient survival time, and increase mortality risk [1][2][3][5][6][7][8][9][10][11][12] . For women with hormone receptor-positive breast cancer, for example, mortality can reach up to 49% of nonadherents 8 .…”
Section: Introductionmentioning
confidence: 99%